Post-Traumatic Diaphragmatic Hernia Late Diagnosed: A Case Report - Drumond, JoÃƒÂ£o Paulo Nunes; Allegro, Bruna Bianca; Favaro, Murillo de Lima; Ribeiro-Jr, Marcelo Augusto Fontenelle (Journal of Medical Biomedical and Applied Sciences, 2017)
The Post-Traumatic Diaphragmatic Hernia (PTDH) is relatively uncommon and may be caused by blunt, penetrating or iatrogenic trauma. The most commonly herniated abdominal structures are stomach, omentum and colon. The diagnosis is challenging because of nonspecific and low sensibility clinical features; so most cases are diagnosed after an asymptomatic or oligosymptomatic period, allowing visceral strangulation and higher morbidity in chronic phase. This report presents a case of a left posterolateral PTDH diagnosed late in latency phase, after 19 years of the trauma occurrence, manifesting clinically with unspecific and progressive respiratory symptoms.Keywords: diaphragm, diaphragmatic hernia, diagnosis, diagnostic imaging. Â Â